PENGARUH KOMPENSASI, PENDIDIKAN DAN PROGRAM KESEJAHTERAAN TERHADAP PRODUKTIVITAS KERJA WARTAWAN DI PROVINSI BALI - Harliawan, Hendri; Murjana Yasa, I Gusti Wayan; Dewi, Made Heny Urmila (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.07.TAHUN 2017, 2017)
In the province of Bali productivity issues become a problem in itself, especially in the field of journalists. The low compensation in the form of salaries, incentives and social benefits to be subject suspected to affect the low productivity of labor. Therefore, purpose this study to analyze the influence; (1) compensation and education for the employee’s well-being of journalists, (2) compensation, education, work experience and employee’s well-being on work productivity, (3) the effect education to compensation, (4) the indirect effect of education on welfare (5) the indirect effect of compensation and education to work productivity, and (6) the effect moderated work experience to influence education on journalist productivity in Bali.